2021
DOI: 10.1186/s12967-021-02776-8
|View full text |Cite
|
Sign up to set email alerts
|

The value of kidney injury molecule 1 in predicting acute kidney injury in adult patients: a systematic review and Bayesian meta-analysis

Abstract: Introduction The aim of the study was to systematically review relevant studies to evaluate the diagnostic value of urinary kidney injury molecule 1 (uKIM-1) for acute kidney injury (AKI) in adults. Method We searched PubMed and Embase for literature published up to November 1st, 2019 and used the Quality Assessment Tool for Diagnosis Accuracy Studies (QUADAS-2) to assess the quality. Then, we extracted useful information from each eligible study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
0
40
1
1
Order By: Relevance
“…Thus, an expression profile of fibrosis and kidney damage markers was conducted. Our results showed an upregulation of kidney injury molecule-1 (Kim-1) [ 42 ], and an upregulation in the mRNA levels of the transcription factor carbohydrate-responsive element-binding protein b (Chrebpb) , the increase of which has been related to the progression of diabetic kidneys ( Figure 5 a) [ 43 ]. In addition, an upward trend in the expression of fibronectin (Fn-1) , a protein related to fibrotic processes [ 44 , 45 ] was also detected.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an expression profile of fibrosis and kidney damage markers was conducted. Our results showed an upregulation of kidney injury molecule-1 (Kim-1) [ 42 ], and an upregulation in the mRNA levels of the transcription factor carbohydrate-responsive element-binding protein b (Chrebpb) , the increase of which has been related to the progression of diabetic kidneys ( Figure 5 a) [ 43 ]. In addition, an upward trend in the expression of fibronectin (Fn-1) , a protein related to fibrotic processes [ 44 , 45 ] was also detected.…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin (IL)-18, a pro-inflammatory cytokine that induces the production of interferon gamma, is detected in urine after acute proximal tubular damage [ 10 , 22 ]. Urine KIM-1, a transmembrane glycoprotein, is a proven marker of AKI in adults [ 23 ]. NGAL is a key polypeptide found in blood and urine at the time of AKI development after ischemic or toxicity-induced damage in the kidney [ 24 ].…”
Section: Diagnosis Of Akimentioning
confidence: 99%
“…For clinical practice, KIM-1 has been proposed as a biomarker of proximal tubule damage [ 43 ] for predicting AKI, diagnosing AKI, and estimating AKI severity [ 32 ]. A recent meta-analysis involving adult patients reported that KIM-1 was a good predictor of AKI, with an estimated sensitivity of 0.74 (95% credible interval, 0.62–0.84) and specificity of 0.86 (95% credible interval, 0.76–0.90) [ 84 ]. Elevated KIM-1 levels can be measured 12–24 h after tubular injury, peaking at 2–3 days [ 85 ].…”
Section: Application Of New Acute Kidney Injury Biomarkersmentioning
confidence: 99%